PENGEMBANGAN E-BOOK INTERAKTIF “QURANIC QUEST” TERKAIT MATERI MENGAJI DAN MENGKAJI SURAH AT-TIN PADA PEMBELAJARAN PAI KELAS 4 SD - Adzani, Fajar; Taqiyuddin, Amal; Aeni, Ani Nur (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2024)
Islamic education in the digital era demands innovation in teaching methods. This research aims to develop an interactive E-Book "Quranic Quest" which is specifically designed to help students in reciting and reviewing Surah At-Tin in grade 4 elementary school. Islamic Religious Education (PAI) learning needs to be updated innovatively because so far it feels monotonous and tends to be boring for students. Traditionally, PAI lessons often only focus on teaching religious doctrines, without providing a deep and comprehensive understanding of the material presented. This research focuses on developing more interactive and interesting learning methods to increase students' understanding of PAI material. In this case, researchers used the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Through the use of digital technology, the Quranic Quest E-Book includes various interactive features such as quizzes, simulations and animations to strengthen student understanding. Apart from that, this research also includes testing and evaluation of the interactive e-book to measure its effectiveness in supporting the student learning process. The results of the validation test show that the Quranic Quest E-Book received a very positive response from material and learning media experts. The validation test by material experts achieved a score of  100 %, which indicates that the content presented is in accordance with PAI learning standards and is able to provide an in-depth understanding of Surah At-Tin. Meanwhile, validation by media experts reached a score of 90%, indicating that the design and interactive features used are quite effective in attracting students' attention and are easy to use.   Keywords: Development, Interactive E-Book, Surah At-Tin.